Cover Image. Issue 1 (18th January 2020) - Yu, Zhijun; Cheng, Kaihui; He, Hongbin; Wu, Jiaqiang
Abstract : The cover image is based on the Short Communication A novel reassortant influenza A (H1N1) virus infection in swine in Shandong Province, eastern China, by Zhijun Yu et al., https://doi.org/10.1111/tbed.13360 .